Association of the human invariant chain with H-2 Db class I molecules. - Cerundolo, V; Elliott, T; Elvin, J; Bastin, J; Townsend, A (1992)
We describe two proteins of 24 kDa and 33 kDa (p24 and p33) which associate with H-2 Kb and H-2 Db molecules, respectively, in human cells transfected with H-2 Kb and H-2 Db genes. This association is particularly clear in the mutant cell line T2, in which association of endogenous peptide with newly synthesized class I molecules may not occur (V. Cerundolo et al., Nature 1990. 345: 449). We show that p33 is the 33-kDa form of the human invariant chain which is resident in the endoplasmic reticulum of T2 cells (P. Cresswell, Cold Spring Harbor Symp. Quant. Biol. 1989. LIV:309). The stability of the invariant chain H-2 Db complex is critically dependent upon occupation of the class I binding site by peptide ligand. In the absence of peptide, the complex is stable at 4 degrees C whereas following exposure to peptide, the invariant chain dissociates rapidly from H-2 Db molecules (half-life of 30 min at 4 degrees C). Although the interaction between the human invariant chain and murine H-2 Db is unlikely to have any functional significance, the peptide-induced dissociation of the invariant chain is consistent with a conformational change in H-2 Db on peptide binding.